Indoor vs. outdoor airborne element array: A novel approach using moss bags to explore possible pollution sources. (June 2019) - Capozzi, F.; Di Palma, A.; Adamo, P.; Sorrentino, M.C.; Giordano, S.; Spagnuolo, V.
Abstract: This study investigated by the moss-bag approach the pattern of air dispersed elements in 12 coupled indoor/outdoor exposure sites, all located in urban and rural residential areas. The aims were to discriminate indoor vs. outdoor element composition in coupled exposure sites and find possible relation between moss elemental profile and specific characteristics of each exposure site. Elements were considered enriched when in 60% of the sites, post-exposure concentration exceeded pre-exposure concentration plus two folds the standard deviation. Of the 53 analyzed elements, 15 (As, B, Ca, Co, Cr, Cu, Mn, Mo, Ni, Sb, Se, Sn, Sr, V, Zn) were enriched in moss exposed outdoor, whereas a subset of 7 elements (As, B, Cr, Mo, Ni, Se, V) were enriched also in indoor moss samples. The cluster analysis of the sites based on all elements, clearly separated samples in two groups corresponding to mosses exposed indoor and outdoor, with the latter generally exceeding the first. Among outdoor sites, urban were most impacted than rural; whereas other factors (e.g., heating and cooking systems, building material, residence time and family life style) could affect element profile of indoor environments. Based on the indoor/outdoor ratio, As derived from outdoor and indoor sources, B, Mo and Se were enriched mostly in outdoor sites; Ni, Cr and V were specifically enriched in most indoor samples, supporting the presence of indoor emitting sources for these elements. A PCA of all indoor sites based on enriched elements and site characteristics showed that traffic affected indoor pollution in urban areas. The moss bag approach provided useful information for a global assessment of human exposure. Graphical abstract: Image 1 Highlights: Indoor vs. outdoor trace element composition was tested in coupled sites by moss bags. Indoor element profile consisted of a subset of the elements accumulated outdoor. The I/O ratio indicated different element source for indoor and outdoor samples. Ni, Cr and V were specifically enriched in most indoor samples. Building features, fireplaces and life style affected indoor element profile. Abstract : The indoor element profile detected by moss bags was found to be a sub-set of the outdoor one.